2019
DOI: 10.1177/1060028019835843
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Direct Oral Anticoagulant Population Management Tool on Anticoagulation Therapy Monitoring in Clinical Practice

Abstract: Background: The optimal monitoring and follow-up strategy for long-term direct oral anticoagulant (DOAC) therapy has not been established. Historically, at our medical center, DOAC patients were referred to a clinical pharmacy specialist managed anticoagulation clinic (AC) for monitoring via regularly scheduled encounters (face-to-face or telephone). Objective: To determine if implementation of a DOAC Population Management Tool (PMT) designed to identify patients who most likely require clinical review and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…The need for updated laboratory monitoring was frequently and consistently identified throughout follow‐up. Population‐based management tools have been developed to assist with DOAC monitoring on a broad scale and can be helpful for identifying the need for updated labs or adjusted doses based on renal function or drug‐drug interactions for high risk patients 29‐34 . While these tools can be helpful at a population level, and include markers of adherence such as MPR or PDC in addition to flagging patients on potentially inappropriate doses or needing updated laboratory monitoring, they cannot replace patient‐level evaluations of adherence.…”
Section: Discussionmentioning
confidence: 99%
“…The need for updated laboratory monitoring was frequently and consistently identified throughout follow‐up. Population‐based management tools have been developed to assist with DOAC monitoring on a broad scale and can be helpful for identifying the need for updated labs or adjusted doses based on renal function or drug‐drug interactions for high risk patients 29‐34 . While these tools can be helpful at a population level, and include markers of adherence such as MPR or PDC in addition to flagging patients on potentially inappropriate doses or needing updated laboratory monitoring, they cannot replace patient‐level evaluations of adherence.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this improved efficiency, the time to generate an intervention (eg, flag review and subsequent intervention if appropriate versus patient visit, assessment and subsequent intervention) was reduced by 75% (16 minutes versus 64 minutes). 6 In a similar project, Chau reported that incorporating the DOAC PMT into their practice model resulted in a tripling in the number of clinical interventions occurring in 86% less time than standard clinic‐based monitoring. 7 In 2017, May et al reported a 41% increase in pharmacy efficiency after a DOAC PMT‐based practice model was implemented, reporting that the model “… allowed the CPS [clinical pharmacy specialists] to target interventions to high‐risk patients and complete interventions by chart review rather than telephone encounter, thus reducing the workload of the CPS.” 8 The same year, Tolley et al reported, “Clinical pharmacists were able to globally manage a large number of patients prescribed DOACs at the Ralph H. Johnson VA Medical Center and make 1142 interventions in 699 patients (56% of the DOAC population) within a 2.5 month time period.” 9…”
Section: Impact and Success Of The Initiativementioning
confidence: 99%
“…This study will help explore the impact of population health tools for safe anticoagulant medication management in a variety of different clinical contexts use, these tools address one critical component (appropriate dosing) in an efficient manner [22]. Such tools are currently being used for population-based management of patients with diabetes [23].…”
Section: Contributions To the Literaturementioning
confidence: 99%